Case reports on a gastric mass presenting with regional lymphadenopathy: A differential diagnosis is gastric schwannoma - Wadhawan, Arnav (Int J Surg Case Rep, 2020)
BACKGROUND: Gastric schwannomas are uncommon among a broad range of possible diagnoses in the work up of a gastric mass. Regional lymphadenopathy associated with gastric schwannoma is an even less common occurrence and one would otherwise suspect a malignant neoplasm. CASE PRESENTATION: We present two non-consecutive cases from a signle academic center depicting Caucasian females in their 5th and 6th decades of life with gastric schwannoma and adjacent lymphadenopathy. Multiple lymph node excisions were performed without evidence of neoplasia. DISCUSSION: Lymphadanopathy in the presence of a gastric mass typically represents malignant neoplasm. A less than likely presentation of gastric schwannoma with reactive regional lymph nodes poses a challenge to adequate preoperative diagnosis and increases risk for a more aggressive than necessary surgical approach with lymphadenectomy. CONCLUSION: While the correlation between gastric schwannoma and lymphadenopathy is uncertain, this ought to be considered. If diagnosis can be confirmed preoperatively, omission of lymphadenectomy is appropriate.